Strategic Innovation in Sharia Governance: The Evolving Management Role of the Sharia Supervisory Board - Septy Rahma Dwi; Febria Lesmita; Suzana Suzana; Muhammad Albahi; Siti Intan Nurdiana Wong Abdullah; Silvia Sari Sitompul (Yayasan Pendidikan Islam Al-Matani, 2024)
The Shariah Supervisory Board (DPS) plays a vital role in ensuring that the operations and financial products of Islamic financial institutions comply with Shariah principles. This research aims to explore the roles, responsibilities, and challenges faced by DPS through analyzing the available literature. Through the literature study method, this research analyzes various secondary sources, including scientific articles, books, regulations, and reports from Islamic financial institutions. The results show that DPS has a key role in providing trust to stakeholders, but also faces various challenges, such as the lack of uniform global standards and limited resources. This study provides recommendations to strengthen the role of DPS, including improved training and education of DPS members, as well as harmonization of regulations at the international level. Thus, DPS can be more effective in supporting the sustainable growth of the Islamic finance industry in accordance with Islamic principles.